COMPARATION OF DIAGNOSTIC VALUE B-MODE ULTRASOUND WITH COLOR DOPPLER TWINKLING ARTIFACT FOR DETECTING RESIDUAL STONE AFTER PCNL - Wardhana, Sonny Andikha; Rizaldi, Fikri; Djojodimedjo, Tarmono; Hardjowijoto, Sunaryo (Indonesian Journal of Urology, 2017)
Objective: To compare the accuracy of B-Mode US and color Doppler twinkling artifact for detecting residual stone after Percutaneous Nephrolithotomy (PCNL) with Non-contrast CT (NCCT) as the standard diagnostic. Material & methods: In this prospective study, 30 patients who underwent Percutaneous Nephrolithotomy (PCNL) were examined with US and NCCT. In US, echogenicity and posterior-shadow (PS) parameters were evaluated and compared with color-Doppler ultrasonography (CDUS) twinkling artifact and NCCT signs. The results then analyzed statistically with Kappa and McNemar tests. Results: More positive residual stone results with color Doppler twinkling artifact in 14 patients than B-Mode US in 11. NCCT detected 17 residual stone with the most location in inferior calyx. (n=10, 58.8%). The sensitivity, specificity and difference positive-negative likehood ratio of B-Mode US were 64.7%, 92.3% and 8.02, both Kappa test was significant (p=0.125) and McNemar tests was significant (p=0.002). The color Doppler twinkling artifact has 82.3%, 92.3%, and 10.5 for sensitivity, specificity and difference positive-negative likehood ratio, the Kappa test was significant (p=0.00), McNemar test was not significant (p=1.00). Conclusion: Color Doppler twinkling artifact was valid, highly sensitive and accuracy better than B-mode US in detecting residual stone after PCNL procedure.